Compliment Rules or Compliments Rule? A Population-Level Study of Appearance Commenting Norms on Social Media - Åberg Erica; Koivula Aki; Kukkonen Iida; Sarpila Outi (Switzerland, 2022)
This study examines norms concerning appearance-related commenting on social media. More specifically, the focus of this study is on the approvability of positively commenting on other people’s physical appearance, commenting on other people’s dressing style and commenting on the appearance of public figures. We examined how these norms are predicted by gender and social media usage patterns, while considering also a set of control variables, including age. We approach these questions with unique data, which is nationally representative of the Finnish population aged 18–74 (N = 3,724). Our study offers insights into the discussion on the relationship between social media and appearance-related norms. Our findings suggest a generally positive attitude towards commenting on other people’s appearance if the comment is positive, with almost half of the respondents approving such commenting. By contrast, commenting on someone’s clothing or commenting on the appearance of public figures is considerably less acceptable, with only 20% approving. Our findings reveal that gender, preferred social networking site and age are associated with appearance commenting norms. Women are more likely to approve of positive appearance commentary on social media. However, the propensity to agree on the approvability of appearance commentary is higher for men when it comes to commenting on other people’s dressing or public figures’ appearances. Overall, the users of Instagram and Facebook seem more liberal towards appearance-related comments as compared to those who do not use social media or use other platforms. Additionally, young people were more positive about appearance commenting in all of these aspects.
Social Computing and Social Media. Participation, User Experience, Consumer Experience, and Applications of Social Computing